Molecular and behavioral profiling of Dbx1-derived neurons in the arcuate, lateral and ventromedial hypothalamic nuclei. Issue 1 (December 2016) - Sokolowski, Katie; Tran, Tuyen; Esumi, Shigeyuki; Kamal, Yasmin; Oboti, Livio; Lischinsky, Julieta; Goodrich, Meredith; Lam, Andrew; Carter, Margaret; Nakagawa, Yasushi; Corbin, Joshua
Abstract Background Neurons in the hypothalamus function to regulate the state of the animal during both learned and innate behaviors, and alterations in hypothalamic development may contribute to pathological conditions such as anxiety, depression or obesity. Despite many studies of hypothalamic development and function, the link between embryonic development and innate behaviors remains unexplored. Here, focusing on the embryonically expressed homeodomain-containing geneDeveloping Brain Homeobox 1 (Dbx1 ), we explored the relationship between embryonic lineage, post-natal neuronal identity and lineage-specific responses to innate cues. We found thatDbx1 is widely expressed across multiple developing hypothalamic subdomains. Using standard and inducible fate-mapping to trace theDbx1 -derived neurons, we identified their contribution to specific neuronal subtypes across hypothalamic nuclei and further mapped their activation patterns in response to a series of well-defined innate behaviors. Results Dbx1 -derived neurons occupy multiple postnatal hypothalamic nuclei including the lateral hypothalamus (LH), arcuate nucleus (Arc) and the ventral medial hypothalamus (VMH). Within these nuclei, Dbx1 + progenitors generate a large proportion of the Pmch-, Nesfatin-, Cart-, Hcrt-, Agrp- and ERα-expressing neuronal populations, and to a lesser extent the Pomc-, TH- and Aromatase-expressing populations. Inducible fate-mapping reveals distinct temporal windows for development of theDbx1 -derived LH and Arc populations, with Agrp+ and Cart+ populations in the Arc arising early (E7.5-E9.5), while Pmch+ and Hcrt+ populations in the LH derived from progenitors expressingDbx1 later (E9.5-E11.5). Moreover, as revealed by c-Fos labeling, Dbx1 -derived cells in male and female LH, Arc and VMH are responsive during mating and aggression. In contrast, Dbx1 -lineage cells in the Arc and LH have a broader behavioral tuning, which includes responding to fasting and predator odor cues. Conclusion We define a novel fate map of the hypothalamus with respect toDbx1 expression in hypothalamic progenitor zones. We demonstrate that in a temporally regulated manner, Dbx1 -derived neurons contribute to molecularly distinct neuronal populations in the LH, Arc and VMH that have been implicated in a variety of hypothalamic-driven behaviors. Consistent with this, Dbx1 -derived neurons in the LH, Arc and VMH are activated during stress and other innate behavioral responses, implicating their involvement in these diverse behaviors.